Wnt Signaling in Atherosclerosis: Mechanisms to Therapeutic Implications - Rizwana Afroz; Julie E. Goodwin (Biomedicines, 2024)
Atherosclerosis is a vascular disease in which inflammation plays a pivotal role. Receptor-mediated signaling pathways regulate vascular inflammation and the pathophysiology of atherosclerosis. Emerging evidence has revealed the role of the Wnt pathway in atherosclerosis progression. The Wnt pathway influences almost all stages of atherosclerosis progression, including endothelial dysfunction, monocyte infiltration, smooth muscle cell proliferation and migration, and plaque formation. Targeting the Wnt pathway to treat atherosclerosis represents a promising therapeutic approach that remains understudied. Blocking Wnt signaling utilizing small molecule inhibitors, recombinant proteins, and/or neutralizing antibodies ameliorates atherosclerosis in preclinical models. The Wnt pathway can be potentially manipulated through targeting Wnt ligands, receptors, co-receptors, and downstream signaling molecules. However, there are challenges associated with developing a real world therapeutic compound that targets the Wnt pathway. This review focuses on the role of Wnt signaling in atherosclerosis development, and the rationale for targeting this pathway for the treatment of atherosclerosis.